THU0379 Coronary artery disease in sle: a case-controlled angiographic study. (12th June 2018) - Chazal, T.; Kerneis, M.; Guedeney, P.; Haroche, J.; Mathian, A.; Ruffat, P.; Cohen-Aubart, F.; Montalescot, G.; Amoura, Z.
Abstract : Background: Coronary artery disease (CAD) is a major cause of morbidity and mortality in systemic lupus erythematosus (SLE) patients. 1 Whether SLE is a cardiovascular risk factor per se remains controversial. Objectives: This study was conducted to determine the clinical and angiographic characteristics of SLE patients with CAD and to compare them to those of control non-SLE patients with CAD. Methods: All SLE patients who underwent a coronary angiography procedure in our tertiary centre between 2005 and 2016 were enrolled in the study. Those without significant atherosclerosis (stenosis >50%) were excluded. Each SLE patient was matched by sex and age at catheterization with seven non-SLE controls with significant CAD. Angiographic characteristics were reviewed by two independent cardiologists. Results: Among the 73 SLE patients who underwent coronary angiography, 28 patients had at least one significant coronary atherosclerotic lesion. The SLE patients were predominantly female (75%, median age of 55.7 years) with a long-standing disease duration (median SLE duration of 20.5 years). Ten patients (35%) had renal involvement, and 9 patients (32%) had antiphospholipid syndrome. The patients with SLE had fewer cardiovascular risk factors (1.6 vs 2.1, p=0.01) than the controls, including lower body mass index (23.8 kg/m² vs 24.98 kg/m², p=0.03), less frequent family history of coronary artery disease (3.5% vs 18%, p=0.049) and less diabetes (7% vs 22%, p=0.07) than controls. However, SLE patients were more likely to have chronic kidney failure (35% vs 20%, p=0.07) and to need hemodialysis (17% vs 2%, p=0.001). The SLE patients more often had multivessel disease (50%). Conclusions: While they have fewer cardiovascular risk factors, patients with SLE experience more severe CAD than non-SLE patients, suggesting that SLE, associated conditions or the treatments themselves play key roles in the development of atherosclerosis. 2 References: [1] Lee YH, Choi SJ, Ji JD, Song GG. Overall and cause-specific mortality in systemic lupus erythematosus: an updated meta-analysis. Lupus2016Jun;25(7):727–734. [2] Schoenfeld SR, Kasturi S, Costenbader KH. The epidemiology of atherosclerotic cardiovascular disease among patients with SLE: a systematic review. Semin Arthritis Rheum2013Aug;43(1):77–95. Disclosure of Interest: None declared